LITERATURE REVIEW: KNOWLEDGE LEVEL, DIETARY ATTITUDE TO INCREASED BLOOD GLUCOSE IN PEOPLE WITH DIABETES MELLITUS - Lathifah Siti Nuraini; Nining Sriningsih; Rina Puspita Sari (Universitas Muhammadiyah Ponorogo, 2023)
Diabetes mellitus is a disease that many people suffer from, coupled with this disease it is also a degenerative disease which has a mortality rate of 3% each year. To control blood glucose levels, it is necessary to improve diet, one of which is by choosing the right foods. Apart from that, knowledge and attitudes about diet can influence increasing blood glucose levels in diabetes mellitus sufferers. The purpose of this study was to understand the relationship between the level of knowledge and the attitude of eating patterns towards increasing blood glucose levels in people with diabetes mellitus in the community. This research is an analytical research based on literature studies and article searches through online search sites, namely through the Indonesian library site and searches using Google Scholar, EBSCO, Science Direct. This study found that the higher the level of knowledge of Diabetes Mellitus patients about diet, their blood sugar tends to be well controlled, because diabetes mellitus patients with a high level of knowledge tend to easily implement the management of diabetes mellitus in their daily lives